The Influence of the Spiritual Leadership Style of the Principal and the Organizational Climate on the Psychological Welfare of State Elementary School Teachers in North Penajam Paser Regency - Suryadi, Suryadi; Roesminingsih, Erny; Widiyanah, Ima; Khamidi, Amrozi (Journal of English Language and Education, 2026)
This study aims to empirically analyze the influence of the principal's spiritual leadership style and organizational climate on the psychological well-being of elementary school teachers in Penajam Paser Utara Regency in the context of transformation towards the Capital City of the Archipelago. The approach used is quantitative with an associative causal type Explanatory Survey design. The study population was 1,128 teachers, with a sample of 296 respondents determined using the Slovin formula and Stratified Random Sampling technique. Data were collected through a structured questionnaire using a 4-point Likert Scale, then analyzed by multiple linear regression through SPSS, including classical assumption tests, partial tests, simultaneous tests, and coefficients of determination. The results showed that spiritual leadership style had a positive and significant effect on teachers' psychological well-being (β = 0.786; p 0.05), as did organizational climate (β = 0.681; p 0.05). Simultaneously, both variables had a significant effect with an F value of 156.761 (p 0.05). An R-square value of 0.515 indicates that 51.5% of the variation in teacher psychological well-being can be explained by these two variables. This finding underscores the importance of value-oriented leadership and a conducive work climate in improving teacher psychological well-being amidst the dynamics of regional change.